Effects of dietary antimicrobial peptides on intestinal morphology, antioxidant status, immune responses, microbiota and pathogen disease resistance in grass carp Ctenopharyngodon idellus. (April 2022) - Liu, Shulin; Wang, Shaodan; Liu, Xuewei; Wen, Liufa; Zou, Jixing
Abstract: This study aims to highlight the effects (8 weeks) of dietary antimicrobial peptides (AMPs, a compound of 6 kDa and 5 kDa from intestine) on intestinal morphological functions and health status in grass carp ( Ctenopharyngodon idellus ). Fish were supplemented with various gradient concentrations of AMPs, including M0 (0 mg/kg), M1 (100 mg/kg), M2 (200 mg/kg), M3 (400 mg/kg), M4 (800 mg/kg) and M5 (1600 mg/kg). Our results showed that amylase, lipase, chymotrypsin enzymatic levels, and total antioxidant capacity (T-AOC) were significantly increased ( p < 0.05), while malondialdehyde (MDA) content was significantly decreased in the intestines of the AMP treated groups compared to the M0. Histological analysis revealed villus height and crypt depth of foregut and midgut in the M4 group were significantly different ( p < 0.05) compared to the M0. In the M3 group, the gene expression levels of IL-1β were significantly up-regulated, while levels of IL10 and TGF-β were significantly down-regulated than other treated and control groups. The abundance of Firmicutes was significantly increased ( p < 0.05), while the Planctomycetes abundance was decreased at phylum level in M1-M5 groups. Subsequent to the AMP treatment, fish were injected with Aeromonas. hydrophila to assess disease resistant potential. In A. hydrophila injected M3-group, the gene expressions of IL-1β, IL8, and TNF-α were significantly down-regulated while that of TGF-β was significantly up-regulated, and IL10 showed no significant difference compared to the control. Further, AMPs also increased the abundance of the Acidobacteria, Proteobacteria, and Patescibacteria, and decreased the abundance of the Fusobacteria and Firmicutes. Therefore, dietary AMPs (400–800 mg/kg) boosted intestinal health by promoting intestinal morphology, digestive and antioxidant capacities, immunity, and intestinal microbiota in C. idellus . Highlights: Antimicrobial peptides boosted intestinal health by promoting intestinal morphology. Antimicrobial peptides could enhance digestive and antioxidant capacities on grass carp. Antimicrobial peptides could improve immunity, and intestinal microbiota on grass carp. Antimicrobial peptides can be used as the substitute of antibiotics.